2016
DOI: 10.21101/cejph.a4231
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Factors Affecting Frequency of Intestinal Parasites in Primary School Students in an Urban Region in Turkey

Abstract: SUMMARYAim: The aim of the study was to determine the incidence of intestinal parasitic diseases (IPD) and associated factors in primary school students and to assess the knowledge and practices of mothers about these diseases.Methods: This is a cross-sectional study carried out in January-March 2014 in 471 students aged 5-11 years, studying at 3 schools randomly selected from the city centre regions with different socioeconomic levels. Stratified sampling method was used in the present study and the data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…According to the WHO, over two billion people are currently harboring IPI throughout the world [46]. Poor deprived commu-nities with low socioeconomical and educational status, where improper waste and sewage management, poor hygienic habits, limited access to clean water supply, and ignorance of appropriate personal practices are more prone to IPI dissemination [42,45,[47][48][49][50][51]. In Kuwait and other Arabian Gulf countries, many expatriates and residents originate from these parts of the world thus implementing a great risk factor to the spread of intestinal parasites due to occupational nature [1,5,51].…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO, over two billion people are currently harboring IPI throughout the world [46]. Poor deprived commu-nities with low socioeconomical and educational status, where improper waste and sewage management, poor hygienic habits, limited access to clean water supply, and ignorance of appropriate personal practices are more prone to IPI dissemination [42,45,[47][48][49][50][51]. In Kuwait and other Arabian Gulf countries, many expatriates and residents originate from these parts of the world thus implementing a great risk factor to the spread of intestinal parasites due to occupational nature [1,5,51].…”
Section: Discussionmentioning
confidence: 99%
“…Osman et al [ 14 ] reported that the consumption of untreated water triples the risk of protozoal infections compared to water treated with chlorite. In addition, the consumption of uncooked fruits and vegetables after washing with contaminated water tends to also increase the risks of intestinal protozoan infections [ 23 ], as well as limited access to clean water and adequate sanitation facilities such as toilets [ 24 ]. Similarly, extreme poverty and low economic level are also predictors for protozoal infections occurrence [ 25 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Jakarta Barat merupakan daerah perkotaan (urban) dengan kepadatan penduduk tertinggi di provinsi DKI Jakarta. [11][12][13] Tujuan penelitian ini adalah mengetahui prevalensi infeksi cacing usus di daerah rural dan urban.…”
Section: Pendahuluanunclassified